The psychological process and emotional cognition of children's tourism experiences in Chinese family culture - Guo, Xuanxuan; Liu, Tao (Frontiers in Public Health, 2022)
The family cultural environment affects children's cognitive development and socialization processes, and different family cultural environments lead to differences in children's tourism experiences. The current research on children's tourism experiences demands a shift from the families' perspective to that of children's perspective. In response to this, grounded on the cognitive development theory, this paper, from the perspective of children's memorable parent-child tourism experience, uses 321 children's drawings to project the tourism elements, people, activities, scenes, and colors that children perceive from travel, reveals the main cognitive contents of children's parent-child tourism experiences. Furthermore, this paper analyzes the influence of family cultural background on children's tourism experiences through interviews with children. Our results show that with the growth of age, children's perception of elements changes from the macro level to the micro level, and the contents they perceive change from concrete to abstract. In addition, children have an acute perception of people and are impressed by novel activities during travel. They adapt well to changes in travel scenes and prefer bright and vibrant colors during trips. Therefore, we recommend the design of appropriate tourism products that combine the characteristics of children's experiences when offering parent-child travel programs, as well as upgrading the market of parent-child tourism experiences through novel activities.